SELF-REPORTED MORBIDITY AND BURDEN OF DISEASE IN UTTAR PRADESH, INDIA: EVIDENCE FROM A NATIONAL SAMPLE SURVEY AND THE MILLION DEATHS STUDY. Issue 4 (5th October 2015) - Yadav, Ajit Kumar; Gouda, Jitendra; Ram, F.
Summary: Uttar Pradesh is India's most populous state with a population of 200 million. Any change in its fertility and mortality is bound to bring change at the national level. This study analysed the burden of disease in the state by calculating the disability-adjusted life year (DALY) for infectious and non-communicable diseases. Data were from two rounds (52 nd and 60 th ) of the National Sample Survey Organization (NSSO) survey conducted in 1995–96 and 2004, respectively, and the Million Deaths Study (MDS) of 2001–03. Descriptive and multivariate analyses were carried out to identify the determinants of different types of self-reported morbidity and DALY. The results show that in Uttar Pradesh the prevalence of all selected self-reported infectious and non-communicable diseases increased over the study period from 1995 to 2004, and in most cases by more than two times. The highest observed increase in prevalence was in non-communicable diseases excluding CVDs, which increased from 7% in 1995 to 19% in 2004. The prevalence was higher for those aged 60 and above, females, those who were illiterate and rich across the time period and for all selected morbidities. The results were significant at p <0.001. The estimation of the DALY revealed that the burden of infectious diseases was higher during infancy, noticeably among males than females in 2002. However, females aged 1–5 years were more likely to report infectious diseases than corresponding males. The age distribution of the DALY indicated that individuals aged below 5 years and above 60 years were more susceptible to ill health. The growing incidence of non-communicable diseases, especially among the older generation, puts an additional burden on the health system in the state. Uttar Pradesh has to grapple with the unresolved problem of preventable infectious diseases on the one hand and the growth in non-communicable disease on the other.